Press freedom and censorship during Covid-19 pandemic: the case of Cebu City - Baba, Kenneth Michael M; Alkuino, Kent Andrei S.; Tictic, Ezra P.; Dungog-Cuizon, Ana Leah Dungog-Cuizon (Faculty of Communications Science, Dr. Soetomo University, 2022)
Censorship, in all its forms, has always been a means by which freedom is being checked and regulated. In hindsight, for the state and its people, censorship must always be exercised with caution to avoid suppression of the constitutionally guaranteed freedom of the press. Moreover, freedom of the press is crucial in times of crisis, as in the case of a global pandemic named COVID-19. The Philippines, regarded as the world's texting capital and one of the widest in social media use, feel the convenience of getting the news right at the fingertips, apart from avoiding physical contact in compliance with health protocols. The study zeroes in on Cebu City, regarded as one of the country's largest voting populations and a newsmaker in terms of its policies vis-a-vis the pandemic. It delves into the juxtaposition of press freedom and censorship in Cebu City against the backdrop of the pandemic. This study is anchored on Bunn’s New Censorship Theory, Scammel’s foundations on the Index of Censorship, and the ever-developing Libertarian Theory. Further, it employed the Colaizzi method to explore the experiences of Cebu-based media practitioners and media institutions. In this vein, press freedom and censorship are not mutually exclusive. The presence of one does not preclude the other; they can actually co-exist. The exercise of press freedom very well depends on the personal values of the media practitioners and institutions.